Production of ACE inhibitory peptides from sweet sorghum grain protein using alcalase: Hydrolysis kinetic, purification and molecular docking study. (15th May 2016) - Wu, Qiongying; Du, Jinjuan; Jia, Junqiang; Kuang, Cong
Highlights: A kinetic model for the alcalase hydrolysis behavior of sweet sorghum grain protein was proposed. The peptide was identified as TLS, and its IC50 value is 102.1 μM. TLS could effectively interact with the active site of ACE. The ACE inhibition of TLS is mainly attributed to its C-terminal Ser. Abstract: In this study, sweet sorghum grain protein (SSGP) was hydrolyzed using alcalase yielding ACE inhibitory peptides. A kinetic model was proposed to describe the enzymolysis process of SSGP. The kinetic parameters, a and b, were determined according to experimental data. It was found that the model was reliable to describe the kinetic behaviour for SSGP hydrolysis by alcalase. After hydrolysis, the SSGP hydrolysate with DH of 19% exhibited the strongest ACE inhibitory activity and the hydrolysate was then used to isolate ACE inhibitory peptides. A novel ACE inhibitory peptide was successfully purified from this hydrolysate by ultrafiltration, ion exchange chromatography, gel filtration chromatography, and reversed-phased high performance liquid chromatography (RP-HPLC). The amino acid sequence of the purified peptide was identified as Thr–Leu–Ser (IC50  = 102.1 μM). The molecular docking studies revealed that the ACE inhibition of the tripeptide was mainly attributed to its C-terminal Ser, which can effectively interact with the S1 and S2 pockets of ACE. Our studies suggest that the tripeptide from the SSGP hydrolysate can be utilized to develop functional food ingredients or pharmaceuticals for prevention of hypertension.